Keanekaragaman Jenis Ikan di Lebak Petai Pedamaran Ogan Komering Ilir - Ria Fahleny; M. Ilham Firmansyah; Anita Karolina (Universitas Sumatera Selatan, 2023)
Lebak Petai is a place for fishing by fishermen and auction holders. A continuous fishing system can affect the diversity of fish in these waters. The aims of this research was to identify the type of fish, length and weight of the fish, analyze the species diversity index, uniformity index, relative abundance, dominance and water quality. This research was carried out from July to September 2021. Sampling took place in Lebak Petai, Pedamaran sub-district, Ogan Komering Ilir district, using three sampling stations. The results of the research showed that there were 530 types of fish caught in Lebak Petai, consisting of 13 types of fish belonging to 9 families. The largest fish in length and weight was the Barbonymus schwanenfeldii fish, namely 12-25.5 in length and 21.11- 188.92 in weight, while the lowest fish was the Elops mchnata fish, namely 9-10.5 in length and 5.58-8.5 in weight. The diversity index was classified as medium, namely 2.33-2.51, the uniformity index was classified as uneven, namely 0.92-0.98, the highest relative abundance in Lebak Petai is Trichogaster pectoralis, and there was no dominant fish, namely between 0.9-0.11. The water quality during the research in Lebak Petai, Ogan Komering Ilir Regency was still within a suitable range for fish life.